2021
DOI: 10.1101/2021.10.09.463764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The initiation of the wound healing program is regulated by the convergence of mechanical and epigenetic cues

Abstract: Wound healing in the skin is a complex physiological process that is a product of a cell state transition from homeostasis to repair. Mechanical cues are increasingly being recognized as important regulators of cellular reprogramming, but the mechanism by which it is translated to changes in gene expression and ultimately cellular behavior remains largely a mystery. To probe the molecular underpinnings of this phenomenon further, we used the downregulation of caspase-8 as a biomarker of a cell entering the wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…In addition to its role in normal development, DNMT3A positively regulates the expression of genes involved in stem cell proliferation and promotes the expression of genes that drive epidermal differentiation 46 . Bhatt et al 47 . demonstrated that after skin injury, cells near the wound edge expressed DNMT3A.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in normal development, DNMT3A positively regulates the expression of genes involved in stem cell proliferation and promotes the expression of genes that drive epidermal differentiation 46 . Bhatt et al 47 . demonstrated that after skin injury, cells near the wound edge expressed DNMT3A.…”
Section: Discussionmentioning
confidence: 99%
“…All cells were maintained, and experiments were performed until passage # 5. Mouse epidermal keratinocytes were harvested from P2/P3 epidermis and were cultured in low calcium E-media to maintain undifferentiated proliferating state as previously described 57 .…”
Section: Methodsmentioning
confidence: 99%